THE INFLUENCE OF SCHOOL WORKING CONDITIONS ON TEACHERS’ JOB SATISFACTION AT A PRIVATE SCHOOL IN SHAN STATE, MYANMAR - Tin Lei Win (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2024)
Purpose: The purpose of this paper is to identify the factors of school working conditions influence teachers’ job satisfaction at a Private school in Shan State, Myanmar and also to examine there is a significant relationship between school working conditions including leadership condition, teacher cooperation, self-efficacy and student discipline and teachers’ job satisfaction at a Private school in Shan State, Myanmar. This study utilizes a quantitative research method to collect data and a total of 60 of full-time teachers from a bilingual private school, in Shan State, Myanmar during the academic year 2024-2025 were surveyed for this study. Multiple Linear Regression was applied for data analysis. The result revealed that specific school working conditions factor has statistically significant influence on teachers’ job satisfaction in a private school at Shan State, Myanmar. Self-efficacy emerged as the strongest influence, accounting for a significant portion of the variance in teachers’ job satisfaction with a Beta value of 0.437(p< 0.001). Additionally, student discipline also had a significant impact on job satisfaction, with a Beta value of 0.2904 (p=0.016). In conclusion, this study recommends that school leaders and principals should prioritize interventions aimed at improving self-efficacy among teachers and fostering a well-disciplined student environment to enhance teachers’ job satisfaction. This approach can lead to more positive outcomes for the school community in Shan State, Myanmar.